Effects of delta9-tetrahydrocannabinol and cannabidiol on a Mg2+-ATPase of synaptic vesicles prepared from rat cerebral cortex. - Gilbert, J C (1977)
1. delta9-Tetrahydrocannabinol and cannabidiol both exhibited a concentration-related inhibition of Mg2+-ATPase of vesicles prepared from synaptosomes isolated from rat cerebral cortex. Cannabidiol was about 3 times more potent than tetrahydrocannabinol. 2. These results were similar to those obtained previously using drugs with well established anticonvulsant activity. 3. Tetrahydrocannabinol at a sub-inhibitory concentration (1 micronM) increased the activity of the Mg2+-ATPase relative to values obtained with vehicle controls.